2001
DOI: 10.1111/j.1469-7793.2001.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated hypoxic exposures change respiratory chemoreflex control in humans

Abstract: A group of seven volunteers (5 male, 2 female) were exposed to 20 min isocapnic (eucapnic) hypoxia once daily for 14 consecutive days. Their chemoreflexes were measured before and after each exposure. The same volunteers repeated the exposures with air substituted for the hypoxic gas mixture in a pseudorandom crossover design. On day 1 an initial ventilatory response to hypoxia and subsequent decline was discernible in two volunteers, but the mean response for all volunteers at this stage was not significant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 34 publications
3
34
2
Order By: Relevance
“…In that study, P ET CO 2 was further reduced after two more nights of hypoxia, suggesting that chronic hypocapnia was progressively developed, which is typical during the early phase of ventilatory acclimatisation. Additionally, it has been reported that central chemosensitivity is enhanced following chronic hypoxia exposure lasting 48 h Tansley et al 1998), but not after 2 weeks of daily intermittent hypoxic exposures lasting 20 min (Mahamed and Duffin 2001). A limitation to our study, though, is that we did not conduct a measure of central chemosensitivity.…”
Section: Discussionmentioning
confidence: 85%
“…In that study, P ET CO 2 was further reduced after two more nights of hypoxia, suggesting that chronic hypocapnia was progressively developed, which is typical during the early phase of ventilatory acclimatisation. Additionally, it has been reported that central chemosensitivity is enhanced following chronic hypoxia exposure lasting 48 h Tansley et al 1998), but not after 2 weeks of daily intermittent hypoxic exposures lasting 20 min (Mahamed and Duffin 2001). A limitation to our study, though, is that we did not conduct a measure of central chemosensitivity.…”
Section: Discussionmentioning
confidence: 85%
“…The decrease in ⌬V E/⌬PET O 2 we observed might also have occurred because the peripheral chemoreflex threshold gradually decreased from the first to the last hypoxic episode. Although increases in the peripheral chemoreflex threshold have not been documented during exposure to intermittent hypoxia, increases have been observed during exposure to short periods of sustained hypoxia (31). Nonetheless, we believe that it is unlikely that decreases in peripheral chemoreflex sensitivity and/or increases in the chemoreflex threshold are responsible for the decreases in ⌬V E/⌬PET O 2 observed.…”
Section: Women Menmentioning
confidence: 77%
“…Thus IH or CH induces some adaptation at the muscle level and lowers MCAv and cerebral oxygenation during hypoxic exercise, potentially mediated by the greater hypocapnia, rather than a compromise in CA or MCAv reactivity. hypoxia; exercise; intermittent and continuous hypoxia; cerebral blood flow ELEVATIONS IN VENTILATORY sensitivity to hypoxia following exposure to either continuous hypoxia [CH, e.g., high altitude (7, 35)] or intermittent hypoxia [IH (11,20,28,42)] results in subsequent hypocapnia (i.e., reduction in end-tidal CO 2 ). Because hypocapnia results in cerebral vasoconstriction (23,32), elevations in ventilatory chemosensitivity may result in cerebral hypoperfusion.…”
mentioning
confidence: 99%